2010
DOI: 10.1177/1934578x1000501020
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin-Rich Black Currant Extract Suppresses the Growth of Human Hepatocellular Carcinoma Cells

Abstract: Dietary antioxidants, such as anthocyanins, are helpful in the prevention and control of various diseases by counteracting the imbalance of oxidative and antioxidative factors in the living systems. Black currant (Ribes nigrum L., Grossulariaceae) is known to contain high amounts of anthocyanins (250 mg/100 g fresh fruit). Black currant fruits have been used in Asian and European traditional medicine for the treatment of a variety of diseases. Black currant extract has recently been found to be the second most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 41 publications
1
30
0
2
Order By: Relevance
“…Although plant extracts differed in their cytotoxic activity (for 72 h incubation), Cy-3-O-Glu at the same concentration as in studied extracts did not show any cytotoxicity, thus cell growth inhibition must have resulted from the exposure to other plant components or more likely their combinations. Our results are in line with the findings of Bishayee et al [35], who showed that anthocyanin-rich fraction of BCur extract exhibited a potent cytotoxic effect in HepG2 cells and this effect was more pronounced than that of delphinidin and cyanidin, two major aglycones of anthocyanins present in BCur. These results indicate that there might possibly be some additive or synergistic effects between components of BCur skin extracts.…”
Section: Discussionsupporting
confidence: 93%
“…Although plant extracts differed in their cytotoxic activity (for 72 h incubation), Cy-3-O-Glu at the same concentration as in studied extracts did not show any cytotoxicity, thus cell growth inhibition must have resulted from the exposure to other plant components or more likely their combinations. Our results are in line with the findings of Bishayee et al [35], who showed that anthocyanin-rich fraction of BCur extract exhibited a potent cytotoxic effect in HepG2 cells and this effect was more pronounced than that of delphinidin and cyanidin, two major aglycones of anthocyanins present in BCur. These results indicate that there might possibly be some additive or synergistic effects between components of BCur skin extracts.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have demonstrated that polyphenols induce DNA damage, and G2/M or G0/G1 cell cycle arrest (16)(17)(18)(19). BCE has been demonstrated to exert an anti-proliferative effect on HT29 colon cancer cells, possibly through the suppression of the cyclin-dependent kinase inhibitor 1 (p21 WAF1 ) signaling pathway (20) and a potent cytotoxic effect against hepatocellular carcinoma (21). However, in the present study, microarray and Ingenuity Pathway Analysis did not indicate suppression of the p21 WAF1 signaling pathway (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Aliment., 16(4), 361-370. http://dx.doi.org/10.17306/J. AFS.2017.0530 www.food.actapol.net/ Bishayee et al (2010) demonstrated that cyanidin--3-O-rutinoside ( Fig. 1), an anthocyanin present in the extract of black gooseberry, could inhibit the growth of liver cancer HepG2 cells.…”
Section: Antioxidants From Berry Fruitsmentioning
confidence: 99%